Effect of Pre-Hydrolysis Reaction Conditions on Xylooligosaccharides Extraction in Eucalyptus Globulus - Cunha, André; Simões, Rogério (KnE Materials Science, 2022)
Pre-hydrolysis-kraft of Eucalyptus globulus by autohydrolysis (batch) and with dilute acid hydrolysis (flow-through reactor) were explored in this study, to examine the recovery of xylooligosaccharides (XOs) from the pre-hydrolysis treatment. The results of this work support the potential reuse of the hydrolysate to increase the recovery yield of added value compounds. The pH of the dilute acid hydrolysis was maintained at 3.5 with acetic acid, to mimic the conditions of the batch reactor medium (autohydrolysis). An increase of XOs recovered was evident when the pre-treatment was in the flow-through reactor instead of the batch reactor. In the latter, a high concentration of furfural was recovered, showing the influence of time in XO conversion through hydrolysis. The total yield of pulp was higher in the flow-through reactor (36.4%) in comparison with the batch system (34.5%) after kraft pulping, which was expected, given the increasing time that the hydrolysate was present in the reactor; however, the difference was small and could have been the result of precipitated compounds in the latter, so this needs further analysis. Keywords: cellulose, Eucalyptus globulus, pre-hydrolysis kraft, xylooligosaccharides